THE EFFECT OF AGE ON DEVEOPMENT OF CONCEPT OF MIND (Journal of the College of Education for Women, 2019)
Educational of the mind is a weapon to a different knowledges whichbenefit in ife and developed the mind in many field and practice him in aregular form in a right thinking and practice sense on exactly recognizing andconception things which is senses and regulating the memory and providingwith benefit information which fit to minded of person,the present researchaimed at answering the following two questions:1-Does the concept of mind differ with age?2-Does the recognition on function of mind developed with development ofage?The research population consisted of the children in the primary schoolsof Baghdad/center,and the students of the Education for womancollege/Baghdad university for the ages(11,18 ,19),the researchsample(22)subjects-was chosen randomly from the statistical population.Thescale consisted of the(37)questions,first question measured thecognition of conception of mind, but(36)questions measured the knowing offunction of mind ,this questios depended on number of the previous literaturesits validity and reliability in the Iraqi population.The following results have been revealed:1-The age of (19)yars obtain on greatest prons in explaination the concept ofthe mind.2-There are a statistically significant differences are shown to a (19) years infunction of mind in contrary to (11, 18)years.On the basis of these results,the researcher has made somerecommendations and suggestions.